Effect of a school-based anxiety prevention program among primary school children - Ab Ghaffar, Siti Fatimah; Mohd Sidik, Sherina; Ibrahim, Normala; Awang, Hamidin; Gyanchand Rampal, Lekhraj Rampal (MDPI, 2019)
Anxiety is one of the most common mental health disorders in childhood, and children with anxiety have an increased risk of psychiatric disorders during adulthood. This study aimed to evaluate the effectiveness of a school-based anxiety prevention program for reducing anxiety among primary school students relative to a school-as-usual control group. Secondary to this, the current study aimed to examine the effect of a school-based prevention program on worry coping skills and self-esteem. A two-group parallel cluster randomized controlled trial of a single-blinded study was conducted to evaluate the effectiveness of the program, with schools as the unit of allocation and individual participants as the unit of analysis. The intervention program was conducted between May 2016 and December 2017. The primary outcome was anxiety, whereas the secondary outcomes were worry coping skills and self-esteem measured at three months post-intervention. Data were analyzed by using a generalized linear mixed model, accounting for the clustering effect. Subgroup analyses were performed for children with anxiety. A total of 461 students participated in this study. At baseline, there was no significant difference between groups for anxiety score, worry coping skills score, and self-esteem score (p > 0.05). The intervention was effective in reducing anxiety for the whole sample (p = 0.001) and the anxiety subgroup (p = 0.001). However, it was not effective in improving worry coping skills and self-esteem. These findings suggest that the program could be effective for reducing symptoms of anxiety when delivered in schools and provide some support for delivering this type of program in primary school settings.